Modeling Human-Induced Loads Through a Calibrated Bipedal Walking Model. Issue 1 (2nd January 2022) - Ruiz, Dianelys Vega; Magluta, Carlos; Roitman, Ney
Abstract: In this paper is proposed a set of empirical equations for parameters and initial conditions of a damped bipedal model with compliant legs. The parameters of the bipedal model are estimated by fitting numerical and experimental walking forces. Sixteen volunteers are recruited to participate in experimental tests to walk on a prototype footbridge. The vertical ground reaction forces (GRFs) induced by pedestrians are recorded by force plates and the accelerations of the structure are recorded by accelerometers. Multiple simulations within certain ranges of input parameters are performed to identify the best matches between the model's predictions and experimentally measured GRFs. Based on empirical data, regression equations are proposed as functions of pedestrian's mass, height, and walking speed. To validate the proposed equations, the experimental tests are simulated, and the predicted structure dynamic responses are compared to measured vibrations on the footbridge. To generate a more realistic pedestrian loading, the gait speed of each step is randomized within a range to reproduce the step-by-step variations. The results of this study validate the suitability of a set of parameters selected for the bipedal model, for use in predicting loads induced by humans and estimating the vibration response of pedestrian structures.